EVALUATION OF ANTIOXIDANT, CAROTENE AND ALKALOID CONTENT IN SPINACH OLERACEA AND ANNONA SQUAMOSA - V.KAVITHA; V.SARADHA RAMADAS (International Journal of Pharma and Bio Sciences, 2015)
The aim of the present study is to determine the antioxidant, carotene and alkaloids content of the selected plant leaves namely spinach oleracea and Annona squamosa. The antioxidant screening was done by DPPH free radical scavenging assay using shade dried leaf extracts. The results showed that IC50 for Annona squamosa and Spinach oleracea was 68.24 (µg/ml), 42.57 µg/ml respectively. Annona squamosa shows highest free radical scavenging activity at the concentration 20µg/ml. Annona squamosa was found to have a maximum amount of carotene (173.24 mg/100gm) followed by Spinach oleracea (58.88 mg/100gm). Regarding alkaloid estimation, Annona squamosa has the highest alkaloid content of 0.48%, while Spinach oleracea had the lowest content (0.03%). Plant antioxidants are believed to play a role in protection against various diseases and delaying ageing processes. Hence the present investigation suggests that medicinal plants which possess good antioxidant potential are the best supplements for the diseases associated with oxidative stress.